Autism in Early Childhood: An Unusual Developmental Course—Three Case Reports. (17th June 2012) - Cohen-Ophir, Michal; Castel-Deutsh, Tsophia; Tirosh, Emanuel
Abstract : Autistic spectrum disorder (ASD) is typically characterized by either an emerging and gradual course or developmental regression in early childhood. The versatile clinical course is progressively acknowledged in recent years. Children with developmental disorders in general are referred to the Child Development Center for a multidisciplinary assessment, investigation, treatment and followup. We report three infants with an initial diagnosis of developmental delays, recovery of normal development following intervention in a multidisciplinary center, and subsequent regression into classic autism following their discharge from the program. An extensive medical workup was noncontributory. This unusual presentation, to our knowledge not reported previously, should be recognized by professionals involved in child development and psychiatry.